Size-dependent resource allocation to reproduction in Japanese anchovies (Engraulis japonicus) - Michio Yoneda; Satoshi Katayama; Masayuki Yamamoto; Naoaki Kono; Tatsuo Tsuzaki; Hiroshige Tanaka (Scientific Reports)
Abstract Size-related changes in reproductive potential are essential for understanding population dynamics and life history strategies; however, the mechanisms driving variation between individuals and sexes remain unclear. Using a diet-switch experiment and carbon and nitrogen stable isotope ratios (SIRs) as quantitative indicators, we investigated how large (parents) and small (offspring) spawning male and female Japanese anchovies (Engraulis japonicus) allocate energy to reproduction. Large individuals of both sexes exhibited higher energy investment in gamete production than small individuals, reflecting a trade-off between growth and reproduction. The turnover rates of SIRs after a diet switch suggest that anchovies predominantly rely on income breeding. However, significant differences in turnover rates between large and small individuals indicate that large fish can also utilize facultative capital resources for gamete production. Notably, males exhibited slower isotopic turnover than females, partly due to the influence of sperm storage. These findings demonstrate that spawning individuals display temporal diversity in resource use for reproduction, with large individuals showing greater flexibility in energy allocation strategies. This study advances our understanding of size- and sex-dependent resource allocation in Japanese anchovy and contributes to a broader understanding of reproductive strategies in small pelagic fishes.